PENGENDALIAN GULA DARAH MELALUI EDUKASI KESEHATAN BAGI PENDERITA DIABETES MELLITUS - Kusyani, Asri (Pusat Penelitian dan Pengabdian kepada Masyarakat, 2025)
Diabetes Mellitus (DM) is a chronic health problem with high blood sugar concentrations because the pancreas can no longer produce insulin or because the body is less able to use the insulin that has been made optimally. If the body is unable to make insulin or does not use it properly, it will result in a spike in blood sugar levels. This activity aims to increase public awareness of high blood sugar levels in DM patients at Jombang Hospital, through health education about DM, The method used is health education about DM disease, The participants of the activity were 39 respondents who were patients diagnosed with diabetes mellitus. The evaluation results showed a decrease in blood sugar levels in DM patients. The results of the study showed that before being given education, all respondents had abnormal blood sugar levels or more than 200 m / dl, namely 39 respondents (100%). blood sugar levels after being given counseling, almost all respondents had normal blood sugar levels, namely 33 respondents (84.6%), and a small portion of respondents had abnormal blood sugar levels, namely 6 respondents (15.4%). respondents are advised to maintain a healthy lifestyle and efforts to control blood glucose levels.